Diversity analysis of BmNPV Isolates Infecting Mulberry Silkworm (Bombyx mori) using Restriction Endonuclease Digestion Profiling - Nagesha, N.; Natesh, J.; Meenakshi, N. H.; Peter, Anitha; Venkataravanappa, V. (International Journal of Bio-resource and Stress Management, 2022)
Understanding the genetic diversity of BmNPV isolates causing grasserie viral disease of mulberry silkworm Bombyx mori L. is essential for adoption of management strategies including biotechnological tools. The present study was aimed at the use of restriction fragment length polymorphism (RFLP) profiling for studying the molecular diversity analysis of six BmNPV isolates collected from Devanahalli, Kolar, Shidlaghatta, Hosakote, Tumakuru, and Ramanagara areas in Karnataka, India (BmNPV-Ko, BmNPV-Ho, BmNPV-SG, BmNPV-DH, BmNPV-TM, BmNPV-Ram respectively). DNA was extracted from each of these isolates and subjected to digestion with different restriction enzymes EcoR1, BamH1, Sma1, Nco1, and a combination of BamH1+Nco1 and electrophoresed in 0.8% w/v agarose gel to visualize restriction enzyme profile. The analysis revealed that all the six BmNPV isolates had similar Nco1 and Sma1 restriction patterns, although there was variation in low molecular weight fragments. The EcoR1 and BamH1restriction patterns were nearly the same for all the isolates except for the presence of an approximately 4kb and an additional 1.5kb polymorphic band only in BmNPV-TM and BmNPV-Ram isolates. BamH1+Nco1 digestion of the DNA from each isolate yielded numerous fragments, which was different in BmNPV-Ram isolate. Molecular diversity analysis can helps in understanding the evolution and phylogeny of the virus, enhance the knowledge on its pathogenicity and can help to develop and adopt suitable measures to combat and diagnose the disease to reduce crop loss and increase income generating ability of the farmer.